THE EFFECT OF LONG-TERM RELATIONSHIP AND PROCESS INTEGRATION ON COMPANY PERFORMANCE THROUGH SUPPLY CHAIN MANAGEMENT AT PT POMI - Diah Nurhayati Mailasufa; Muhammad Ridwan Basalamah; Eka Farida (Pena Cendekia Insani, 2025)
This study examines the impact of long-term relationships (LTR) and process integration (PI) on company performance, with supply chain management (SCM) as a mediator, using a quantitative approach and Structural Equation Modeling (SEM-PLS). Data from 88 suppliers in PT Paiton Operation and Maintenance Indonesia were analyzed. Results show that PI positively influences SCM, and SCM significantly enhances company performance. LTR, while important, lacks impact when it remains solely contractual and without collaborative planning. SCM is crucial for improving operational efficiency and reducing costs. This research highlights the strategic importance of SCM in linking relational and structural factors to performance outcomes, supporting frameworks like Relational View, Transaction Cost Economics, and Dynamic Capabilities Theory. The study suggests enhancing LTR through collaborative SCM practices and extending PI for optimal performance improvement.